Discovery of a new species of the genus Stygepactophanes from a groundwater-fed spring in southern France (Crustacea, Copepoda, Harpacticoida, Canthocamptidae) - Galassi, Diana M.P. (Zookeys, 2019)
Abstract. A new species of the genus Stygepactophanes Moeschler & Rouch, 1984 (Copepoda, Harpacticoida, Canthocamptidae) is established to accommodate a small canthocamptid population collected from a spring system in the “Parc du Mercantour”, Var catchment, southern France. The population analysed in the present study is defined by a set of morphological characters of the female, namely a very large maxilliped, a rudimentary mandibular palp, P1 with 3-segmented exopod and 2-segmented endopod, a falcate terminal claw of the P1 endopod, dorsal seta of caudal rami inserted on the inner margin, and anal operculum not overreaching the insertion of the caudal rami, thus supporting its assignment into the genus Stygepactophanes. The new species Stygepactophanesoccitanus shows marked differences with the nominotypical species of the genus that was originally described by monotypy with the species Stygepactophanesjurassicus Moeschler & Rouch, 1984. The main diagnostic traits of S.jurassicus are the absence of the P5 and a falcate outer terminal claw of P1 endopod. Stygepactophanesjurassicus also shows a reduced armature of the antennal exopod, bearing one seta, 1-segmented P2–P4 endopods, a reduced armature of P2–P4 exopodal segments 3 (3,4,4 armature elements, respectively), P6 bearing only one long seta, a rounded short and smooth anal operculum. Conversely the female of S.occitanus Galassi & Fiers, sp. n. has a well-developed P5, with rudimentary intercoxal sclerite, together with a falcate outer terminal claw of P1 endopod, antennal exopod bearing two elements, P4 endopod 1-segmented versus 2-segmented in P2–P3, P2–P4 exopodal segment 3 with five armature elements, P6 with three setae of different lengths, rounded anal operculum, bearing 3–4 strong spinules. According to our present knowledge, S.occitanus Galassi & Fiers, sp. n. is assigned to the genus Stygepactophanes as the most conservative solution, waiting for the male to be discovered. The genus Stygepactophanes represents a distinct lineage within the harpacticoid family Canthocamptidae that colonised southern European groundwater, the genus being known only from the saturated karst in Switzerland and a fissured saturated aquifer in southern France. Both species of the genus are stygobites and narrow endemics, the nominotypical species being known from the type locality Source de la Doux in Délemont (Switzerland), and S.occitanus Galassi & Fiers, sp. n. described herein from a spring system of the Var catchment (France).